Augmented Reality and Guided Inquiry to Support 21st-Century Competencies: A Pre- and Post-Study in a Vocational Physics Module - Usmeldi, Usmeldi; Amini, Risda; Fadhilah, Fadhilah; Fadillah, Muhammad Aizri (International Journal of Online and Biomedical Engineering (iJOE), 2026)
This study explores the potential of a physics learning module that integrates augmented reality (AR) and guided inquiry to support vocational students’ development of 21st-century competencies. The module was implemented in three Indonesian vocational high schools involving 100 students, using a one-group pretest–posttest design. Students’ competencies in critical thinking, creativity, communication, collaboration, and digital literacy were assessed using structured performance-based tasks before and after the intervention. Results showed statistically significant pre- and post- improvements across all assessed domains, with the most notable gains observed in collaboration (〈 g〉 = 0.34, d = 0.93) and communication (〈 g〉 = 0.30, d = 0.78). These within-group changes indicate promising patterns of skill development; however, the absence of a control group precludes definitive conclusions about the effectiveness of the intervention. The findings align with previous studies suggesting that immersive technologies may support 21st-century competencies, particularly when integrated within structured, inquiry-based learning environments. Caution is advised in interpreting the results as preliminary rather than conclusive. These insights may inform future instructional designs in vocational education and highlight the need for further research using more rigorous comparative designs across diverse learning contexts.